Results of the asymptotic behavior for a viscoelastic wave equation with nonlinear distributed delay and acoustic conditions in boundary feedback - Choucha A.; Boulaaras S.; Jan R.; Tahat A.N. (Springer Nature, 2025)
This study is concerned with a nonlinear viscoelastic wave equation. Assuming the nonlinear distributed delay feedback influences the boundary coupling through the acoustic boundary conditions. Under suitable assumptions and for the general case of the kernel, we prove the asymptotic behavior of solutions. ? The Author(s) 2024.